Accreditation of nursing schools in Iran and five selected countries: A comparative study - Rajab Dashti-Kalantar; Marzieh Asadizaker; Nasrin Elahi; Maryam Rassouli (Elsevier, 2023)
Accreditation is a model that has been approved for ensuring the quality of education. Ensuring the quality of nursing schools is the most important concern in enhancing the nursing care. The aim of the study was to determine the status and compare the accreditation of nursing schools in Iran with five selected countries. The executive characteristics of accreditation in each country are associated with the government's macro policies in education. Although no clear reasoning is presented for choosing either institutional or programme accreditation in the selected countries, measures can be taken to plan for the implementation of accreditation, with regard to the level of development and the need for nursing profession in Iran.